THE LEADERSHIP STYLE OF TRANSFORMATIONAL INFLUENCE POSITIVELY ON THE PERFORMANCE THE APPARATUS OF LOCAL GOVERNMENTS - Budur Latif (International Journal of Innovations in Engineering Research and Technology, 2021)
Transformational leadership always starts with a vision that reflects a common goal, and is explained to all employees in a clear and simple manner, always strives to increase employee awareness of the value and importance of their duties and work for the organization, is oriented towards achieving the vision by maintaining and maintaining the commitment that has been built together, dare to make and respond to changes when needed, and explain to all employees about the benefits of changes made, and develop themselves continuously through various learning media to improve leadership competencies.